2023
DOI: 10.1212/nxi.0000000000200046
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomics Identifies Brain Endothelium Inflammatory Networks in Experimental Autoimmune Encephalomyelitis

Abstract: Background and ObjectivesMultiple sclerosis (MS) is a neuroinflammatory and neurodegenerative disease characterized by infiltration of immune cells in multifocal areas of the CNS. The specific molecular processes allowing autoreactive immune cells to enter the CNS compartment through the blood-brain barrier remain elusive.MethodsUsing endothelial cell (EC) enrichment and single-cell RNA sequencing, we characterized the cells implicated in the neuroinflammatory processes in experimental autoimmune encephalomyel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…To comprehensively characterize the profile of Mcam + BBB ECs, we analysed a dataset of single-cell RNA profiles of ECs isolated from the brains of naïve and MOG 35-55 -immunized EAE animals. 21 Compared to naïve mice, computational analyses first confirmed the increase in Mcam mRNA average expression in brain ECs in EAE mice and further revealed an increase in the frequency of Mcam + brain ECs in EAE ( Fig. 1D ).…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…To comprehensively characterize the profile of Mcam + BBB ECs, we analysed a dataset of single-cell RNA profiles of ECs isolated from the brains of naïve and MOG 35-55 -immunized EAE animals. 21 Compared to naïve mice, computational analyses first confirmed the increase in Mcam mRNA average expression in brain ECs in EAE mice and further revealed an increase in the frequency of Mcam + brain ECs in EAE ( Fig. 1D ).…”
Section: Resultsmentioning
confidence: 66%
“…( D – J ) Analysis of single-cell RNA sequencing dataset of brain ECs in naïve and EAE mice. 21 ( D ) Left and right bar charts show Mcam mRNA expression (mean read per cell ± SEM) in ECs and frequency of Mcam + ECs (mean of total ECs ± SEM), respectively, in brains of naïve and EAE mice. ( E ) Violin plot (log 2 fold change) and ( F ) GSEA of the DEGs in Mcam + ECs in EAE; P < 0.05.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular MRI targeting at P-selectin is used for the detection of BEC activation, which is promising for clinical translation to monitor or even predict the activity and severity of MS, indicating BBB disruption and BEC activation in the early 10.3389/fnins.2023.1047778 stage of MS (Gauberti et al, 2018). Moreover, recent single-cell transcriptomics identified that enhanced adhesive properties and immune transendothelial migration in MS were mainly localized in venous BECs (Fournier et al, 2023).…”
Section: Multiple Sclerosismentioning
confidence: 99%